URGENSI IJTIHAD DALAM MERESPON PERSOALAN KEKINIAN - Abd. Jalil; Zuhri Fahruddin (JOEL: Journal of Educational and Language Research, 2022)
The existence of Islamic law has a very long history and is constantly being challenged to answer the problems that arise in Islamic society. From time to time, the problems that arise are, of course, different between the Islamic community in one region or in one country, and the Islamic community in another region or country. This is due to differences in culture, social, politics, geography, economy, mastery of technology, and other aspects of life. Very often, the problems that arise in the Muslim community cannot be answered explicitly in the Qur'an, al-Hadith, or Ijma`. So, to find the answer, the fiqh scholars did ijtihad. The research method used by the author is a qualitative research method. Qualitative research is research about research that is descriptive and tends to use analysis. Process and meaning (subject perspective) are more highlighted in qualitative research. Ijtihad in jurisprudence is to mobilize all energy and mind to investigate and issue the laws contained in the Qur'an with certain conditions. While the legal basis of ijtihad is the arguments of the Qur'an, al-Hadith, and Ijma`. As for someone who does ijtihad or expert ijtihad called mutjahid. However, there is an opinion that the door to ijtihad is now closed. This opinion is certainly irrelevant if you look at the current problems that continue to arise in a society that has not received legal certainty from Islamic teachings. Therefore, the ijtihad of the mujtahids still has urgency and is still needed.